The Impact of Evoking Models of Peaceful Coexistence in The History of Islam, Achieving Moderation and Building Peace - Al-Karboly, Muheneid Hamad Ahmed (Dirasat: Human and Social Sciences, 2023)
Objectives: The research highlights Islam's dedication to protecting the rights of other religions and minorities. This commitment is exemplified in the preservation of Prophet Muhammad's agreement with the Jews in the Medina Charter, even in their absence during its signing. Additionally, Prophet Muhammad emphasized principles for coexistence, fostering a harmonious life without conflicts among diverse religions, ethnicities, or tribes. Methods: This research adopts an advanced scientific writing approach, drawing from over forty narratives in Islamic history to explore peaceful coexistence. The accuracy of these narratives is ensured through cross-referencing with historical sources and current observations. The study is divided into two sections for a thorough review and analysis. Results: Islam's rulings exhibit fairness towards non-Muslims, notably in the just treatment of Jews and the people of the covenant with granted rights. Societal cohesion relies on collaboration built on mutual understanding. Addressing global poverty necessitates embracing an Islamic financial system. Resolving conflicts and entrusting outcomes to Allah, adhering to the principle "To you, your religion, and to me, mine," is crucial. Vigilance against conspiracies under the banners of tolerance, religion, and equality is essential. Conclusion: Islam demonstrates fairness towards non-Muslims, emphasizing justice for all. This is evident in its impartial treatment of Jews and covenant people, ensuring their religious rights and protection. Authorities worldwide, including those in Iraq, must adhere to Islamic law for peaceful coexistence. Embracing the Islamic financial system is crucial to addressing global poverty.